Sol-Gel Preparation of Highly Water-Dispersible Silsesquioxane/Zirconium Oxide Hybrid Nanoparticles - Yoshiro Kaneko; Tomoyuki Arake (International Journal of Polymer Science)
Highly water-dispersible silsesquioxane/zirconium oxide hybrid nanoparticles (SQ/ZrO2-NPs) were prepared by the following two-step reactions. First, a mixture of 3-aminopropyltrimethoxysilane (APTMOS) and zirconium tetra-n-butoxide (ZTB) was stirred in a mixed solvent of 0.1 mol/L methanolic hydrochloric acid and n-butanol at room temperature, followed by heating in an open system until the solvent was completely evaporated. Then, the aqueous solution obtained by adding water to the resulting product was heated in an open system until the water was completely reevaporated. The products (SQ/ZrO2-NPs) obtained with a feed molar ratio of APTMOS/ZTB of more than 0.3 were dispersed well in water, and their aqueous dispersions were highly transparent, which was confirmed by UV-Vis measurements. In addition, the solid product obtained by drying its aqueous dispersion was redispersed in water. The volume-average particle sizes of SQ/ZrO2-NPs (APTMOS/ZTB ≥ 0.3) were assessed to be ca. 4.6–23.8 nm by dynamic light scattering measurements in water. The theoretical refractive index of the SQ/ZrO2-NP (APTMOS/ZTB = 0.3) was estimated to be 1.66. It was assumed that the water-dispersible property of the SQ/ZrO2-NPs probably originated from the ZrO2-SiO1.5(CH2)3Cl- core-shell structures.